Development of a â€œPocket Book For Prospective Bridesâ€ as an Effort to Improve the Knowledge and Attitudes of Reproductive Health of Prospective Brides in Padang City - Iffah, Uliy; Hijradesy, Laila; Sabrina, Rani (Universitas Andalas, 2023)
Healthy pregnancy _ need preparation physical and psychological for a person woman. Stage this is the most vulnerable period for happening various that problem will influence the condition baby to be born later. this _ could occur because a woman not enough understand the importance of preparation self on period pre conception consequence lack of knowledge possessed . _ Aim from study this is for look influence counseling health developed media _ about health reproduction to knowledge and attitude of catin woman in preparation pre -marriage in the working area of the KUA District Koto Tangah City of Padang on year 2022. Kind study this is Pre Experiment with design One Group Pretest-Posttest . Collection data done on month October â€“ November 2022. Population in study this is whole paint woman who will married in the KUA . Amount sample study this is as many as 40 subjects . Taking sample done with technique Purposive Sampling . Data processing is done with the Paired Sample T- Test (p<0.05) . Research results show that there is difference score average knowledge and attitude paint woman before given counseling health reproduction that is 71.95 and after given counseling health reproduction score to 81.05. Analysis results paired Samples T-Test obtained mark p.s value (p=0.001). There is influence gift counseling health reproduction to knowledge and attitude paint woman . There is influence counseling health reproduction to knowledge and attitude paint woman in preparation pre -marital marriage in the working area of the KUA , Koto Tangah District , Padang City. Expected with study this , government local could do cooperation with party related for make special program in KUA about preparation pregnancy.